The dynamic impact of FX interventions on financial markets - Menkhoff, Lukas,Rieth, Malte,Heidland, Tobias (Collaborative Research Center Transregio 190, 2019)
Evidence on the effectiveness of FX interventions is either limited to short horizons or hampered by debatable identification. We address these limitations by identifying a structural vector autoregressive model for the daily frequency with an external instrument. Applying this approach to the most important, freely floating currencies, we find that FX intervention shocks significantly affect exchange rates and that this impact persists for months. We show for Japan and the US that interest rates tend to fall in response to sales of the domestic currency, whereas stock prices of large (exporting) firms increase after devaluation of the domestic currency.
10419/222102
Keywords: Graue Literatur; Foreign exchange intervention; structural VAR; exchange rates; interest rates; stock prices